Effect of ethanolic seed extract of Croton penduliflorous Hutch. on loperamide-induced constipated male rats (Bangladesh Journal of Pharmacology, 2012)
The laxative effect of ethanolic seed extract of Croton penduliflorous was evaluated in loperamide-induced constipated male rats on daily basis for 7 days. The loperamide significantly (p